Outdoor games as a component of cultivation students-wrestlers’ physical qualities - Dubatovkin, Vladislav I.; Makarova, Elina V. (Физическое воспитание и студенческий спорт, 2023)
Martial arts classes offer the involvement of students in the pedagogical process aimed at mastering knowledge, skills and abilities, the development of model characteristics reflecting the properties and the athlete’s level of readiness, and allowing to achieve the best results. Model characteristics are based on the most significant in training of wrestlers goals and targets that reflect the sportsmen’s objective level, a logically correct theory of sports training, methods of teaching techniques at different stages of training athletes. The modern model of an athlete-wrestler includes the following indicators: characteristics of the training process (intensity and volume of loads), and the level of preparedness (tactical, technical, physical and psychological). Not the least role in the development of modern wrestlers’ physical qualities is played by properly selected outdoor games included in the plan of the training process. An important component in the selection of outdoor games is the development of such physical qualities as strength, endurance, agility, flexibility, speed. It is proved experimentally in the article.